Blaze of light : the inspiring true story of Green Beret medic Gary Beikirch, Medal of Honor recipient - Brotherton, Marcus (WaterBrook, 2020)
"From one of the fiercest skirmishes of the Vietnam War to years of seclusion in a mountain cave, Medal of Honor recipient, Gary Beikirch has faced more than his fair share of battles and overcome each of them through perseverance and faith. He inspires readers to do the same"--